(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
The lichen biota of the Amadiya and Rowanduz districts in the Mountain physiogeographic region in Iraq was sampled in 2013. The samples provided 47 species belonging to 29 genera and 14 families. Among them 37 species are new records for Iraq. All species except Lichinella cribellifera and Thelidium sp. were found in Amadiya district whereas only 13 species occurred in Rowanduz district. Most of the species (59.5%) were crustose, while 27.6% were foliose, 12.7 % squamulose and none fruticose. The three most species-rich genera are Caloplaca with 7 species, Collema with 5 species and Aspicilia with 3 species; 6 genera were represented by 2 species and 20 by single species. All saxicolous lichens were calciphilic while the corticolous lichens were acidophilic. The most common and dominant species is Lecanora muralis, found in all 17 studied locations. Keywords: Lichens; Iraq; Physiogeographic regions; Mountain region. Bangladesh J. Plant Taxon. 24(1): 2332, 2017 (June)